Satisfaction with care quality and anxiety among family members during nursing home visiting restrictions: The chain mediating effect of emotional regulation and perceived stress - Zhaozhao Hui; Xiaoqin Wang; Xun Wang; Jinping Zhao; Yunjin Pan; Feng Liu; Ruishi Zheng; Mingxu Wang (Frontiers Media S.A., 2023)
IntroductionThis study aimed to investigate the psychological well-being (perceived stress and anxiety) of Chinese family members during nursing home visiting restrictions and to elucidate the relationships among satisfaction with care quality, emotion regulation, perceived stress, and anxiety.MethodsAn online survey was conducted with a cross-sectional study design. From 18 to 29 January 2022, a total of 571 family members of nursing home residents completed online questionnaires comprising socio-demographic characteristics, satisfaction with care quality, emotion regulation, perceived stress, and anxiety. Mediation analyses were performed to estimate the direct and indirect effects of satisfaction with care quality on anxiety using the PROCESS macro for SPSS.ResultsThe results showed that approximately one-quarter of Chinese family members had anxiety symptoms during nursing home visiting restrictions. Satisfaction with care quality affected anxiety via three mediating paths: (a) through cognitive reappraisal (effect = 0.028); (b) through cognitive reappraisal and perceived stress sequentially (effect = −0.057); and (c) through perceived stress (effect = −0.212). The chain mediating effect (path b) accounted for 23.7% of the total effect.ConclusionsThese findings corroborated our hypothesis that cognitive reappraisal (a kind of emotion regulation strategy) and perceived stress mediated the relationship between satisfaction with care quality and anxiety during nursing home visiting restrictions. Efforts to address family members' psychological well-being by focusing on cognitive reappraisal should be considered.